Dynamic Response of Bridge-Landslide Parallel System under Earthquake - Yu Liang; Honggang Wu; Tianwen Lai; Hao Lei; Mingzhe Zhu; Kun Ma; Zhiyang Ji; Jiankai Ren (Advances in Civil Engineering)
In order to further understand the instability mechanism and geohazard causation when the main sliding path of the slope body is parallel to the path of the bridge, the corresponding bridge-landslide parallel system is constructed for shaking table tests. This paper summarizes the combination forms of bridge-landslide model under different position and focused on the slope body located above the bridge deck. Firstly, based on the shaking table test results of El Centro (1940), the failure behavior of bridge-landslide parallel system was evaluated, and the changes of acceleration and deformation of bridge pile were subsequently analyzed. Then, the interaction bridge structure and sliding body were explained by the spectral features. The main conclusions are as follows. First, in the model test, the landslide belongs to the thrust-type landslide. Due to the barrier function of the bridge, the main failure site of landslide occurs in the middle and trailing edge of slope body. At the same time, the acceleration value of earthquake waves is 0.3 g, which is the key to this variation. Second, the acceleration response of the measuring points on the bridge pile and landslide increases with the increase of ground elevation. If the slope structure is damaged severely, the deformation response of weak interlayer is inconsistent with the surrounding soil structure. Third, with the increase of excitation power, the dominant frequency of bridge-landslide parallel system gradually transitions from low to high frequency rate, and the interaction of the parallel system weakens the influence of river direction on frequency. Finally, under the same working condition, the dynamic response of the measuring points has obvious regularity with the change of situation. But the response of the same points is not regular due to the different earthquake excitation intensity.